PERANAN PERENCANAAN FISIK DALAM PENGEMBANGAN PERMUKIMAN SKALA BESAR PANTAI TIMUR SURABAYA - Timoticin Kwanda (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 1999)
To fulfil the increase needs of housing especially at large cities, the government encourages developers to develop large scale housing developmets. Large scale housing developments fastly advance at large cities, such as Surabaya. This paper reviews the role of physical planning in developing large scale housing development of Pantai Timur Surabaya project. The project was developed through a long stage, from a preliminary stage to construction stage. In each stage of development, physical planning performs substantial roles with different level of involvement. It is hoped that by understanding the role of physical planning in each stage of large scale housing development, inputs could be reached for developing of large scale housing in the future. Abstract in Bahasa Indonesia : Untuk memenuhi kebutuhan permukiman yang terus meningkat terutama di kota-kota besar, pemerintah mendorong pihak pengembang untuk mengembangkan permukiman skala besar. Pembangunan permukiman skala besar oleh pengembang berkembang cepat di kota-kota besar seperti Surabaya. Tulisan ini membahas tentang peranan perencannaan fisik dalam pengembangan permukiman skala besar proyek Pantai Timur Surabaya. Proyek ini dikembangkan melalui suatu proses tahapan yang panjang mulai dari tahap persiapan sampai dengan tahap pembangunan. Dalam setiap tahapan pengembangan ini, perencanaan fisik cukup berperan dengan tingkatan peran yang berbeda-beda pada setiap tahapan. Dengan mengetahui peranan perencanaan fisik dalam setiap tahapan pengembangan permukiman skala besar ini, diharapkan dapat memberi masukan dalam pengembangan permukiman skala besar di kemudian hari. Kata kunci: Pengembang, Permukiman Skala Besar, Perencanaan Fisik.